Energy performance and climate dependency of technologies for fresh water production from atmospheric water vapour. Issue 8 (26th June 2020) - Peeters, Robin; Vanderschaeghe, Hannah; Rongé, Jan; Martens, Johan A.
Abstract : Solving the water scarcity problem by enhancing water extraction from air technology. Abstract : Extraction of water vapour from atmospheric air and condensing it to liquid water for human usage is an imaginative solution to the water scarcity problem. Atmospheric water vapour is a large and readily accessible fresh water source able to fulfil human water needs. Many systems that draw water vapour from the air with water collecting surfaces, desiccant materials such as zeolites, silica gels, MOFs, polymers and salts and aids such as membranes have been proposed. Much progress has been made in increasing water harvesting efficiency, reducing cost and improving applicability especially in the extreme atmospheric conditions of arid regions. But all these systems are energy intensive and this energy demand for water production is an important element of the water-energy nexus. In this paper the intrinsic energy requirements of water vapour capturing processes in different atmospheric conditions are quantified as the specific water yield (L kW −1 h −1 ). Distinction is made between passive systems that use natural phenomena like solar energy directly, and active systems with human transformation of the energy vector. The generation of thermoelectric energy involves water use and may even lead to overall water consumption instead of production. Technologies involving air cooling to provoke condensation of the water vapour reach specific water yields of 1–4 L kW −1 h −1 but their application is strongly dependent on atmospheric conditions. A specific water yield of 0.1–1 L kW −1 h −1 is commonly achieved for an ad/absorption–desorption cycle with a desiccant material. Depending on climate conditions, either passive systems with desiccants or active cooling of condensation surfaces is energy wise the optimum choice. The intrinsic energy requirements of atmospheric water harvesting are more than hundred times larger than seawater desalination. Fundamentally new concepts are needed to make atmospheric water an affordable fresh water source.